Validation of a German version of the Caregiver Quality of Life Index-Cancer (CQOLC) in a sample of significant others of breast and gynaecologic cancer patients - Ehmann, Anna Tamara; Mahler, Cornelia; Klafke, Nadja (Psicologia, 2020)
There is no disease-specific instrument to measure the quality of life of significant others of cancer patients in Germany. In this study, we evaluated the reliability and construct validity of a German version of the Caregiver Quality of Life Index-Cancer (CQOLC) in a sample of 212 caregivers of breast and gynaecologic cancer patients. The CQOLC was administered along with the World Health Organization Quality of Life short version (WHOQOL-BREF) to caregivers of patients taking part in a randomized-controlled intervention study. Data of 212 caregivers were gained at the baseline of the study. Internal consistency was determined by Cronbach’s α. Construct validity was examined by conducting a confirmatory factor analysis (CFA) and hypothesis testing. Correlations between change scores with patients’ global health-related quality of life (HRQoL) were calculated for three time points to evaluate the responsiveness. The three subscales “burden”, “disruptiveness”, and “financial concerns” indicate to a good reliability of the instrument (Cronbach’s α ranged between 0.754 and 0.832), while the subscale “positive adaptation” demonstrated low reliability (α = 0.579). A CFA based on data from the whole set of CQOLC items resulted in CFI levels < .90, and a CFA without problematic items resulted in CFI levels also < .90.
Gesehen am 09.10.2020